Aeroelastic stability of a flexible ribbon rotor blade. (November 2016) - Sicard, Jerome; Sirohi, Jayant
Abstract: This paper describes the static and dynamic aeroelastic behavior of a thin ribbon that is used as an extremely flexible helicopter rotor blade. The non-dimensional torsional stiffness of this rotor blade is three orders of magnitude lower than that of a conventional helicopter rotor blade. As a result, the rotor blade undergoes large torsional deformation and its static and dynamic behavior are dominated by centrifugal forces. An aeroelastic analysis is developed based on Euler–Bernoulli beam theory including large twist angles and unsteady aerodynamics including the effect of returning wake. The flow is assumed to be attached at all times, and only classical divergence and flutter stability are evaluated. The analysis is validated with deformation measurements of a 23 cm diameter rotor with ribbon blades. Divergence and flutter stability boundaries are identified, and the effects of rotational speed, rotor diameter, location of blade center of gravity and blade pitch are discussed. The analysis can be used as a design tool for flexible ribbon rotors in a variety of missions.